Therapeutic Drug Monitoring in Oncology: International Association of Therapeutic Drug Monitoring and Clinical Toxicology Recommendations for 5‐Fluorouracil Therapy. Issue 3 (11th September 2018) - Beumer, Jan H.; Chu, Edward; Allegra, Carmen; Tanigawara, Yusuke; Milano, Gerard; Diasio, Robert; Kim, Tae Won; Mathijssen, Ron H.; Zhang, Li; Arnold, Dirk; Muneoka, Katsuki; Boku, Narikazu; et al.
Abstract : 5‐Fluorouracil (5‐FU) is dosed by body surface area, a practice unable to reduce the interindividual variability in exposure. Endorsed by the International Association of Therapeutic Drug Monitoring and Clinical Toxicology (IATDMCT), we evaluated clinical evidence and strongly recommend TDM for the management of 5‐FU therapy in patients with colorectal or head‐and‐neck cancer receiving common 5‐FU regimens. Our systematic methodology provides a framework to evaluate published evidence in support of TDM recommendations in oncology.